Preparation of Folic acid@Arsenic Nanoparticles and Evaluation of their Antioxidant Properties and Cytotoxic Effects - Shakibaie, Mojtaba; Faraji, Maryam; Ranjbar, Mehdi; Adeli-Sardou, Mahboubeh; Jabari-Morouei, Fereshteh; Forootanfar, Hamid (Pharmaceutical Nanotechnology, 2024)
Introduction: In this study, arsenic nanoparticles containing folic acid (FA@As NPs) were synthesized by microwave irradiating a mixture of As2O3 and sodium borohydride solution in the presence of folic acid. Methods: The physicochemical characteristics of the prepared NPs were studied by UV–visible spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR) analyses. Antioxidant activities, hemocompatibility, and cytotoxic effects of the prepared NPs were then evaluated. The attained results showed that the hexagonal FA@As NPs have a size range between 12.8 nm and 19.5 nm. Results: The DPPH scavenging activity of FA@As NPs was found to be significantly greater than that of As NPs at concentrations ranging from 40 µg/mL to 2560 µg/mL (p<0.05). The hemolytic test confirmed that the measured hemolysis percentage (HP) for FA@As NPs and As NPs was 0% at concentrations between 20 to160 µg/mL, and for FA@As NPs, the measured HP was not significantly higher than As NPs at concentrations higher than 320 µg/mL (p>0.05). Discussion: The necessary concentration for the death of half of the cells (IC50) for MDA-MB-231, MCF-7, and HUVEC cells treated (24 h) with FA@As NPs was measured to be 19.1±1.3 µg/mL, 15.4±1.1 µg/mL, and 16.8±1.2 µg/mL, respectively. However, further investigations are necessary to clarify the mechanisms behind the biological activities of FA@As NPs.
Keywords: hemocompatibility